The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1183/09031936.00084310
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and noncommunicable diseases: neglected links and missed opportunities

Abstract: Globally, the incidence of tuberculosis (TB) is declining very slowly, and the noncommunicable disease (NCD) burden for many countries is steadily increasing. Several NCDs, such as diabetes mellitus, alcohol use disorders and smoking-related conditions, are responsible for a significant proportion of TB cases globally, and in the European region, represent a larger attributable fraction for TB disease than HIV. Concrete steps are needed to address NCDs and their risk factors. We reviewed published studies invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 112 publications
1
90
0
4
Order By: Relevance
“…[19][20][21][22][23][24] In the present study, in addition to a history of previous TB treatment and young age, several factors independently associated with MDR-TB were identified. For example, HIV-positive TB cases were found to have a significantly higher risk of MDR-TB than their HIV-negative counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…[19][20][21][22][23][24] In the present study, in addition to a history of previous TB treatment and young age, several factors independently associated with MDR-TB were identified. For example, HIV-positive TB cases were found to have a significantly higher risk of MDR-TB than their HIV-negative counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…In HIV/AIDS era, tuberculosis cases have increased probably due to the fact that HIV/AIDS is an immunosuppressive condition hence increasing the risk of contracting the disease. Several studies have also found associations between TB and presence of other chronic infections [13,14]. [15,16], more risk factors to contracting tuberculosis include malnutrition, diabetes, silicosis, alcoholism and tobacco smoking.…”
Section: Respondents Who Suffer From Other Chronic Illnessesmentioning
confidence: 99%
“…Productivity at community level would also increase because of the low mortality and morbidity due to TB decrease. The overall would be increase in economic growth, improved life expectancy and a healthy Nation [6]. Mwea west Sub-County covers an area of approximately 231Km2 with a population of approximately 100, 000 people which accounts for about 19% of the total county population [7].…”
Section: Introductionmentioning
confidence: 99%
“…It should be enhanced into an active cases finding through screening program, one of them is to the high-risk population such as diabetes mellitus (Raviglione, 2010). DM weakens the body's immune responsesand thus can increase the risk for TB infection (Creswell et al, 2011). Since 2015, NTP initiates the TB screening program to DM patient.…”
Section: Introductionmentioning
confidence: 99%